Effect of Pressure and Temperature Changes under Static Conditions on Liquid-Gas Bands - Ismayilov, G.G.; Jahangirova, Kh.T. (Herald of Azerbaijan Engineering Academy, 2024)
One of the most important conditions is that when transporting liquefied gasses, the pressure must not be allowed to fall below the saturation pressure. The formation of a vapor (gas) phase in the pipeline not only increases energy costs, but also adversely affects the safety of transportation. Since the process of transporting liquefied gas is very sensitive to changes in ambient temperature and pressure in the system, any changes in temperature and pressure in both static and dynamic conditions cause serious changes in the liquefied gas pipeline. This effect also affects its volume and other macroscopic parameters associated with the physicochemical properties of liquid gasses. Taking into account the above, the changes caused by pressure and temperature factors in liquefied gas pipelines are investigated. The article shows the significant influence of the temperature factor on the change in pressure under static conditions in a pipeline transporting liquefied gas, and the importance of taking it into account.